Meningkatkan Availability Floating Hose SPM 165.000 DWT Menggunakan Inovasi Floating Hose Stabilizer untuk Menjaga Security of Supply BBM BBK Nasional - Wicaksono, Aziz; Fridana, Hari; Nurjaya, Dalih Fajar; Priyambodho, Bambang Adhi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Single Point Mooring (SPM) 165,000 DWT (Deadweight Tonnage) is a facility at PT Kilang Pertamina Internasional RU VI Balongan that is used for unloading crude oil from tankers to storage tanks. This SPM is about 15 km from the jetty of PT KPI RU VI Balongan which is connected to two parallel 32 inch diameter submarine pipelines. The SPM is connected to 2 floating hoses of 16 inch diameter and 2 submarine hose strings using a turred system connected to 32 inch submarine pipelines through a PLEM. The PLEM is equipped with valves that can be controlled from the SPM using a control umbilical. The existing condition of the 165,000 DWT SPM was idle and unattended. During this period, two strings of floating hose tangled with each other and damaged the floating hose due to abrasion from overlapping. The occurrence of tangling on the floating hose at the same time and repetitive caused to lose and the 165,000 DWT SPM could not be operated and had an impact on the supply of crude oil to the PT KPI RU VI Balongan. In addition, floating hose leaks cause oil spills and pollute the surrounding aquatic environment and require large recovery costs to clean up the oil spills. This research aims to reduce the risk of tangling between 2 floating hoses by applying a floating hose stabilizer at several floating hose joints. The research method begins with a survey of existing floating hose conditions that experience tangling. Furthermore, analysis and modeling of the floating hose system is carried out. Then design and fabrication of floating hose stablizer for tangling prevention. And the results of the analysis and field conditions after the installation of the floating hose stabilizer are reduced potential tangling on 2 floating hoses thereby reducing the risk of losses both financial and environmental.